Evaluación de los factores que influyen en la elección de la bicicleta como modo de transporte en barranquilla incluyendo variables latentes (2018)
Promotion of urban cycling has emerged as a strategy for improving mobility in cities, reducing the carbon footprint, decreasing pollution levels and consolidating sustainable lifestyles. A clear understanding of the key factors influencing the individual bicycle choosing is essential for developing effectives policies towards encouraging the use of this mode of transportation. On the present work an integrated choice and latent variable model with sequential estimation approach was used to determine the factors that influence on choosing the bicycle as mode of transportation. Through a stated preference survey, applied in the city of Barranquilla, northern Colombia, individual information about socioeconomic data, attitudes, perceptions and preferences towards cycling, was captured. An exploratory and confirmatory factor analysis were conducted, and six latent variables were extracted (safety awareness, desire for commodity, desire for economy, environmental awareness, perception towards bicycling and willingness to use bicycle). Lately, a MIMIC model was used to estimate the structural equations of the latent variables. Overall, the results show that the factors influencing the choosing of the bicycle in Barranquilla are: sex, access to a bicycle, the slope, traffic level, temperature, the existence and type of infrastructure, perception towards bicycling, desire for economy and environmental awareness. Subsequently, results indicate that the non-segregated infrastructure, which is the one existent in the city, might not be very attractive to people.